Depression Events Associated with Proton-Pump Inhibitors in Postmarketing Drug Surveillance Data - Tigran Makunts; Haroutyun Joulfayan; Kenneth Ta; Ruben Abagyan (MDPI AG, 2023)
Proton-pump inhibitors, PPIs, are widely prescribed and are available over the counter for prolonged reduction of stomach acid production and related disorders. PPIs irreversibly inhibit the hydrogen/potassium ATPase in gastric parietal cells. Recent retrospective studies have described an association between PPI use and depression. However, there is conflicting evidence that PPI therapy improves depressive symptoms. Considering the widespread use and over-the-counter availability of these drugs, further investigation into depression adverse event was warranted with a larger-scale postmarketing set of reports. Here we analyzed over 125,923 reports from the FDA Adverse Event Reporting System consisting of PPI and histamine-2 receptor antagonist monotherapy records and found a statistically significant association between use of PPIs and depression. Additionally, we analyzed each of the six currently marketed PPIs individually and observed the association with the depression adverse reaction for all of them.